Research Data Governance. The Need for a System of Cross-organisational Responsibility for the Researcher’s Data Domain - Carolin Odebrecht (Data Science Journal)
The integration of research data management into academic workflows presents significant challenges for researchers, resulting in fragmented responsibility and accountability. This essay delves into the complexities surrounding the research data life cycle, revealing gaps in the existing governance systems. Researchers often encounter obstacles such as missing ethical approvals, inadequate data hosting solutions, and inconsistent data transfer regulations, all of which hinder their progress. These issues stem from a disconnection between the institutional governance structures and the practical needs of individual researchers. Current data policies in academic institutions place an overwhelming responsibility on researchers to manage the entire data life cycle, while leaving support frameworks ambiguous. This lack of coordinated responsibility structures hinders effective data management and governance. To address these challenges, the article proposes the development of a research-centric data governance system. This system aims to bridge the gap between institutional policies and discipline-specific requirements. By implementing a research data governance system, researchers can gain control over data ownership and align it with their research objectives.